2018
DOI: 10.1111/cbdd.13198
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and in vivo wound healing potential of phenolic extracts from jaboticaba skin

Abstract: In this study, different phenolic extracts were obtained from the jaboticaba skin meal (JSM), whose phenolic compounds were characterized and their antibacterial activities were assessed. Moreover, the activity of lyophilized ethanolic extract of jaboticaba skin (EEJS) on wound healing was analyzed in rats. The JSM phenolic extracts were obtained in four ways: aqueous, methanolic, ethanolic, and acetone extracts. The phenolic compounds were characterized in these extracts by high-performance liquid chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
(35 reference statements)
0
8
0
1
Order By: Relevance
“…A study showed that the doses of phenol around 10-15 mg/L had toxicity (29). Nevertheless, the CS-LS 1% as the lowest concentration, effectively prevented the growth of bacteria such as Escherichia coli, and Salmonella and prevented the production of histamine (30,31).…”
Section: Groupmentioning
confidence: 99%
“…A study showed that the doses of phenol around 10-15 mg/L had toxicity (29). Nevertheless, the CS-LS 1% as the lowest concentration, effectively prevented the growth of bacteria such as Escherichia coli, and Salmonella and prevented the production of histamine (30,31).…”
Section: Groupmentioning
confidence: 99%
“…In this context, the mechanism of action of phenolic compounds on pathogenic bacteria is not yet well known. According to Machado and co-workers [33], tannins and flavonoids can inactivate enzymes due to the formation of complexes with proteins and cell wall from bacteria, changing their cell membrane permeability.…”
Section: Ta Extractsmentioning
confidence: 99%
“…2 In addition, the bark and leaves of M. cauliflora are used to treat diarrhea. 3 Previous pharmacological studies on extracts of this plant showed antioxidative, 4,5 antibacterial, 6 antiinflammatory, 7 and cytotoxic activities. 8 Phytochemical investigations were mainly focused on its fruits, which led to the isolation of some phenolic derivatives.…”
mentioning
confidence: 94%
“…In addition, the bark and leaves of M. cauliflora are used to treat diarrhea . Previous pharmacological studies on extracts of this plant showed antioxidative, , antibacterial, anti-inflammatory, and cytotoxic activities . Phytochemical investigations were mainly focused on its fruits, which led to the isolation of some phenolic derivatives. , As a continuation of investigations on structurally unusual and bioactive metabolites from Myrtaceae plants, three rearranged triketone–terpene adducts with new skeletons, myrcaulones A–C ( 1 – 3 ), were obtained from the leaves of M. cauliflora .…”
mentioning
confidence: 99%